Perancangan Aplikasi Pengelolaan Data Pegawai Berbasis Mobile Menggunakan Kodular dan Airtable - Ira Murni; Putri Ratricia; Muhammad Dedi Irawan (Bulletin of Computer Science Research, 2024)
CABJARI Deli Serdang is a branch of the North Sumatra District Attorney's Office which was formed in several regions, one of which is in Pancur Batu to facilitate the duties and authorities given. At the agency, in processing employee data, they still use Excel and web applications. So with that, this research makes a mobile-based system to process employee data to be more effective and efficient. The goal is to create accurate information including promotion or class, academic status, and position mutations and mutations between regions through the existing system. The system is made using the waterfall development method, through planning, design, implementation (development), and testing. The platforms used are Kodular and Airtable, Black box testing is used as a testing stage for the program that will be implemented, the test proves the system runs well. The results of this study produce a system design that can be developed to facilitate employee performance in managing employee data, where work can be done anywhere and anytime because the system is mobile-based.